Current and future perspective of registry utilisation for regulatory settings in Japan: pharmaceuticals, medical devices, and regenerative medicine products - Chieko Ishiguro; Yasutomo Teshima; Harumasa Nakamura (Journal of Pharmaceutical Policy and Practice, 2025)
Considerable attention has been paid to the utilisation of real-world data throughout the lifecycle of pharmaceuticals, medical devices, and regenerative products. In Japan, regulatory initiatives have been implemented to promote the utilisation of real-world data and evidence for regulatory decision-making, especially focusing on the use of disease registries. In this brief article, we outline regulatory initiatives, summarise the current status of registry utilisation in Japanese regulatory settings, and offer points to consider and perspectives on registry utilisation for stakeholder collaboration.